2015
DOI: 10.1002/jbmr.2748
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Atypical Femoral Fractures: Clinical and Geometrical Data

Abstract: Despite the multitude of studies published on atypical femoral fractures (AFFs), a profile for patients at risk does not exist. This study aimed first at estimating AFF incidence over a 19-month-period in Quebec City using the ASBMR Task force criteria to define AFF. The medical records of patients hospitalized for hip or femoral fracture between June 1, 2009, and December 31, 2010, were reviewed. Thirty-six cases of atypical fractures were identified during the 19-month period, representing an AFF incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 41 publications
3
40
1
1
Order By: Relevance
“…24 When used in patients who are at high risk of fracture, these drugs are estimated to prevent 80–5000 fragility fractures for each atypical femur fracture possibly induced by treatment. 65 Several steps can be taken to address this problem, 66 such as improved patient and doctor education regarding both the risk-benefit ratio of these drugs and the prodromal symptoms (eg, groin or hip pain) of atypical femur fractures; potential use of dual x-ray energy absorptiometry to monitor patients on therapy specifically for features of atypical femur fractures; 67 identification of high-risk patients using femur geometrical characteristics and other risk factors for atypical femur fractures; 68 and the development of pharmacogenomic markers identifying patients at increased risk of atypical femur fractures.…”
Section: The Growing Gap In Treatment Optionsmentioning
confidence: 99%
“…24 When used in patients who are at high risk of fracture, these drugs are estimated to prevent 80–5000 fragility fractures for each atypical femur fracture possibly induced by treatment. 65 Several steps can be taken to address this problem, 66 such as improved patient and doctor education regarding both the risk-benefit ratio of these drugs and the prodromal symptoms (eg, groin or hip pain) of atypical femur fractures; potential use of dual x-ray energy absorptiometry to monitor patients on therapy specifically for features of atypical femur fractures; 67 identification of high-risk patients using femur geometrical characteristics and other risk factors for atypical femur fractures; 68 and the development of pharmacogenomic markers identifying patients at increased risk of atypical femur fractures.…”
Section: The Growing Gap In Treatment Optionsmentioning
confidence: 99%
“…Schilcher and colleagues showed ethnic differences in location of the AFFs, with fractures mainly occurring in the subtrochanteric region in Singapore, compared with diaphyseal in Sweden . The differences may be related to femoral geometric parameters that are more common in Asian women, such as increased femoral bowing and smaller neck‐shaft angles . Increased femoral curvature may lead to an altered distribution of loading with more tensile strain on the lateral side and more compression on the medial side of the femur.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be pointed out that patients with AFF may also have other nongenetic factors that may predispose to this type of fracture, such as femoral and/or lower limb deformities. In this sense, recent studies have also suggested a possible contribution of proximal femoral geometry in AFF, reporting either an excessive femoral offset and femoral neck angle in varus, and/or femorotibial valgus deformities in some of these subjects …”
Section: Discussionmentioning
confidence: 98%